Welfare Indicators for Aquaculture Research: Toolboxes for Five Farmed European Fish Species - Chris Noble; Wout Abbink; René Alvestad; László Ardó; Marie‐Laure Bégout; Nina Bloecher; Erik Burgerhout; Josep Calduch‐Giner; Mauro Chivite‐Alcalde; Petr Císař; Evan Durland; Åsa M. Espmark; et al. (Reviews in Aquaculture, 2026)
Refining approaches to measuring, monitoring and appraising animal welfare in aquaculture research is key to (i) protecting and optimizing it, (ii) documenting the severity of how and when it deviates, and (iii) ensuring good scientific quality, reliable results and reproducibility, amongst other factors. However, different fish species and life stages can have varying welfare needs and assessing their welfare can be challenging. An array of welfare indicators (WIs) can be utilized when documenting fish welfare, and there is currently little consensus on which WIs are most applicable to the key fish species used in European aquaculture research. The aim of this review is to propose updated, fit for purpose and comprehensive WI toolboxes for aquaculture research involving Atlantic salmon ( Salmo salar ), rainbow trout ( Oncorhynchus mykiss ), European seabass ( Dicentrarchus labrax ), gilthead seabream ( Sparus aurata ), and the common carp ( Cyprinus carpio ). Where possible, these toolboxes will also include life‐stage considerations. It also provides information on utilizing WIs in deciding humane end‐points as well as information on how to sample different types of indicators. The review closes with information on how digitalization can affect the collection, collation and analysis of WI data in aquaculture research, including both practical and theoretical considerations. The toolboxes incorporate a range of WIs that go beyond those required for legally safeguarding fish welfare in both laboratory and operational experimental facilities in the current European 2010/63/EU Directive on the protection of animals used for scientific purposes and its amendment, the Commission Delegated Directive (EU) 2024/1262.

Higher parasite burdens are associated with lower body condition in a Norwegian moose population - Jaelle C. Brealey; Bjørnar Ytrehus; Erling J. Solberg; Rebecca K. Davidson; Christer Moe Rolandsen (European Journal of Wildlife Research, 2025)
Parasites are ubiquitous in wildlife and can influence health and fitness. Thus, the inclusion of parasites in wildlife monitoring programs could provide important information for understanding declines in population body condition or recruitment rates. However, parasites are often neglected as a factor in wildlife management. We characterised the gastrointestinal parasite community of moose ( Alces alces ) in central Norway over an autumn hunting season and the following winter, using parasitological examination of faecal samples. We identified an age-related effect on parasite communities, including increased prevalence and abundance of Protostrongylidae species and increased community richness in yearlings compared to older moose. We also found that individuals with a lower body mass had higher burdens of Trichostrongylidae and Protostrongylidae species in autumn. There was some evidence for increased parasite burdens in males compared to females, while there was less evidence for seasonal differences between autumn and winter in a subsample of adult females. We found no strong associations between parasite burdens and moose population density. Our results add to the growing body of literature supporting the use of parasite burdens as proxies for an individual’s health status and potentially as predictors for fitness effects. In many Fennoscandian moose populations, the body condition and recruitment rates of individuals are declining, thus further monitoring of parasites may be needed to better understand the mechanisms behind these declines, including the potential role of parasites.

A Review on the Effects of the Doubled Maternal Genome in Triploids With a Suggested Pathway to Improving Their Performance in Aquaculture by Purging Deleterious Genes - Tom J. Hansen; Alison C. Harvey; Angelico Madaro; Aurélien Delaval; Kevin A. Glover; Monica F. Solberg; Thomas W. K. Fraser; Per Gunnar Fjelldal (Reviews in Aquaculture, 2025)
Triploid fish are usually sterile, a trait which reduces unwanted sexual maturation in fish farming and eliminates the risk for negative genetic effects of escapees on wild stocks. The triploid state, normally established through a doubling of the maternal genome, consists of two chromosome sets from the mother and one from the father. The increase in genome size is accompanied by an increase in cell volume and reduction in cell number that are associated with physiological effects which have been described in several studies. The doubled maternal genome is also mirrored in the triploid phenotype whereby meristic characters, growth, and physiology, are commonly biased towards that of the dam. However, chromosome doubling techniques are also known to give strong inbreeding effects. In meiotic gynogenes, this is seen in fitness‐related traits such as reduced survival, especially during early life, an increase in deformities, and lower growth. The same effects on fitness, although to a milder degree, are seen in triploids, which supports the hypothesis that they are also affected by inbreeding. Producing triploids by interploidy alleviate the inbreeding problem as the tetraploids can be crossbred to increase their heterozygosity. However, producing tetraploid broodstocks is both challenging and time and resource demanding. An alternative approach is to establish a triploid founder broodstock through one generation of gynogenesis. The gynogenesis will eliminate the lethal alleles, and by selecting the best performing individuals from the best performing families, one will also partially eliminate recessive deleterious alleles, increasing the fitness of the resulting triploid population.

Forest management plan pathways for non-industrial private forest owners in Norway: from acquisition to implementation - Altamash Bashir; Hanne K. Sjølie; Birger Solberg (European Journal of Forest Research, 2024)
Forest management plans (FMP) are key decision-support tools for forest managers and a central policy instrument in many countries. Despite its pivotal importance in forest management, there is a lack of studies that analyze the acquisition, familiarity and implementation of the FMP. These steps collectively contribute to making FMP a successful decision-support tool and forest policy instrument. We surveyed a sample representative of the population of Norwegian non-industrial private forest (NIPF) owners to quantify the importance of a broad set of factors, including ownership objectives, socio-demographic, property and information sources variables on the FMP pathway, i.e. acquisition of FMP, awareness of its content and implementation of the plans’ proposals. Applying principal component analysis on twelve ownership objectives, we found that most forest owners are multiobjective. We combined conditional classification trees and logistic regression analyses on the FMP pathway to unveil familiarity and use of FMP in forest owner subgroups as well as individual drivers. The results indicate that 37% of Norwegian NIPF owners have a FMP. Among the owners having FMP, 66% have good knowledge of its content and 40% implement its proposals. The strongest variables to predict FMP familiarity and use were previous harvests, productive area, advice about forestry from the public management, knowledge of public support schemes for forestry and perceived relevance of the FMP. We conclude that FMP suppliers, consultants, forestry bureaucracy and policy-makers should emphasize information dissemination and relevance of the FMP to increase its success as a decision-support tool and forest policy instrument.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Flanders hapavirus in western North America - Andrew J. Golnar; Stan Langevin; Nicholas A. Panella; Owen D. Solberg; William K. Reisen; Nicholas Komar (Archives of Virology, 2018)

Plasticity in response to feed availability: Does feeding regime influence the relative growth performance of domesticated, wild and hybrid Atlantic salmon Salmo salar parr? - A. C. Harvey; M. F. Solberg; K. A. Glover; M. I. Taylor; S. Creer; G. R. Carvalho (Journal of Fish Biology, 2016)
Growth of farmed, wild and F1 hybrid Atlantic salmon parr Salmo salar was investigated under three contrasting feeding regimes in order to understand how varying levels of food availability affects relative growth. Treatments consisted of standard hatchery feeding ( ad libitum ), access to feed for 4 h every day, and access to feed for 24 h on three alternate days weekly. Mortality was low in all treatments, and food availability had no effect on survival of all groups. The offspring of farmed S. salar significantly outgrew the wild S. salar , while hybrids displayed intermediate growth. Furthermore, the relative growth differences between the farmed and wild S. salar did not change across feeding treatments, indicating a similar plasticity in response to feed availability. Although undertaken in a hatchery setting, these results suggest that food availability may not be the sole driver behind the observed reduced growth differences found between farmed and wild fishes under natural conditions.

Willingness of Nonindustrial Private Forest Owners in Norway to Supply Logging Residues for Wood Energy - Hanne K. Sjølie; Dennis Becker; Daniel Håbesland; Birger Solberg; Berit Hauger Lindstad; Stephanie Snyder; Mike Kilgore (Small-scale Forestry, 2016)

Genetic discontinuities in a continuously distributed and highly mobile ungulate, the Norwegian moose - H. Haanes; K. H. Røed; E. J. Solberg; I. Herfindal; B.-E. Sæther (Conservation Genetics, 2011)

The Role of Wood Material for Greenhouse Gas Mitigation - L. Gustavsson; R. Madlener; H.-F. Hoen; G. Jungmeier; T. Karjalainen; S. KlÖhn; K. Mahapatra; J. Pohjola; B. Solberg; H. Spelter (Mitigation and Adaptation Strategies for Global Change, 2006)

Integrated Monitoring Program on Acidification of Chinese Terrestrial Systems (Impacts) — A Chinese-Norwegian Cooperation Project - D. Tang; E. Lydersen; H. M. Seip; V. Angell; O. Eilertsen; T. Larssen; X. Liu; G. Kong; J. Mulder; A. Semb; S. Solberg; K. Torseth; et al. (Water, Air, & Soil Pollution, 2001)

Reactive Nitrogen Compounds at Spitsbergen in the Norwegian Arctic - S. Solberg; T. Krognes; F. Stordal; OØ Hov; H. J. Beine; D. A. Jaffe; K. C. Clemitshaw; S. A. Penkett (Journal of Atmospheric Chemistry, 1997)

On the Spatial Distribution and Seasonal Variation of Lower-Troposphere Ozone over Europe - H. E. Scheel; H. Areskoug; H. Geiss; B. Gomiscek; K. Granby; L. Haszpra; L. Klasinc; D. Kley; T. Laurila; A. Lindskog; M. Roemer; R. Schmitt; et al. (Journal of Atmospheric Chemistry, 1997)

The potential of alley cropping im improvement of cultivation systems in the high rainfall areas of Zambia II. Maize production - R. B. Matthews; S. Lungu; J. Volk; S. T. Holden; K. Solberg (Agroforestry Systems, 1992)